2003
DOI: 10.1172/jci16336c1
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic restrictive cardiomyopathy is part of the clinical expression of cardiac troponin I mutations

Abstract: The authors wish to correct errors that appeared in the Methods section and throughout the paper. The correct sentences are below. The authors regret the errors.Mutation analysis of TNNI3 by direct sequencing identified a 87A→G nucleotide substitution of exon 8 resulting in an Asp190Gly amino acid substitution that segregated with the disease in the family (maximal two-point lode score: 4.8).Direct sequencing of TNNI3 identified a 93G→A nucleotide substitution of exon 8, which resulted in an Arg192His amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 0 publications
3
76
0
2
Order By: Relevance
“…A recent study of over a thousand patients from 16 families diagnosed with HCM found ~1.5% of these individuals had mutations in TNNI3 or MYH7 and functionally presented with restrictive cardiomyopathy underscoring the role of secondary factors in determining clinical outcomes [43]. Furthermore, within a cardiomyopathy classification like RCM there is a range of disease severity [9], which adds to the difficulty of clinically stratifying patients and further complicates understanding the pathogenesis from the cellular manifestations of a diseased allele to the clinical presentation. The evidence of phenotypic variability within kindreds and among patients with the same genotype [9;43;44], in addition to patients presenting with mixed RCM/HCM phenotypes [9] further support the notion that readily distinguishing between HCM and RCM is challenging and that RCM may fall under the broad clinical spectrum of HCM [1;43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of over a thousand patients from 16 families diagnosed with HCM found ~1.5% of these individuals had mutations in TNNI3 or MYH7 and functionally presented with restrictive cardiomyopathy underscoring the role of secondary factors in determining clinical outcomes [43]. Furthermore, within a cardiomyopathy classification like RCM there is a range of disease severity [9], which adds to the difficulty of clinically stratifying patients and further complicates understanding the pathogenesis from the cellular manifestations of a diseased allele to the clinical presentation. The evidence of phenotypic variability within kindreds and among patients with the same genotype [9;43;44], in addition to patients presenting with mixed RCM/HCM phenotypes [9] further support the notion that readily distinguishing between HCM and RCM is challenging and that RCM may fall under the broad clinical spectrum of HCM [1;43].…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of RCM can include early morbidity during childhood with the only treatment in that case being transplantation [7]. Both HCM and RCM can result from mutations in the same gene [9], TNNI3, which encodes for cardiac troponin I (cTnI). With the significant advances in both molecular cardiology and disease diagnosis, clinically stratifying patients into HCM or RCM categories has become challenging as the boundaries between these cardiomyopathic phenotypes are no longer clearly defined [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 A mutation within the troponin I (TNNI3) gene leads to either hypertrophic cardiomyopathy or RCMP within the same family. 15,16 …”
Section: Genetic Findingsmentioning
confidence: 99%
“…In the case of β-ARs, the variability is best illustrated by the differential effects of polymorphisms in the β-ARs on clinical outcome and response to therapy in patients with heart failure [16][17][18]. It is also illustrated for genetic cardiomyopathies, wherein mutations in a given gene could cause the contrasting phenotype of hypertrophic or dilated or restrictive cardiomyopathy [19,20]. Whether there are differences in the sequence, density of the β-ARs or the downstream signaling molecules and their targets between mice and rabbits are unknown.…”
mentioning
confidence: 99%